Strengthening Character Education Through Contextual Teaching and Learning Oriented Lesson Study - Gede Nugraha Sudarsana; Wayan Eka Paramartha; Ni Ketut Suarni; I Wayan Susanta; I Ketut Dharsana; Ulan Sari (Universitas Muhammadiyah Semarang, 2021)
Abstract— The purpose of this study is to find out the strengthening of character education through the application of contextual teaching and learning oriented lesson study in elementary school students in Buleleng Regency. The response in this study was determined randomly, with the total of 50 people consisting of 25 students of State Elementary School 1 Panji and 25 students of Elementary Laboratorium Undiksha. This research includes descriptive analytical. Data collection is done using observation methods and questionnaires. Data analysis uses descriptive statistics. Based on the calculation of the average value of strengthening student character education through contextual teaching and learning oriented lesson study obtained religious values of 76% (very often), nationalist values by 78% (very often), independent values by 74% (often), integrity values of 70% (often), and mutual cooperation values by 85% (very often). The results suggest that linking material to daily activities can help students gain better character education. Lesson study also provides innovative and varied teaching experiences to teachers.Keywords— Strengthening Character Education, Lesson Study